2022
DOI: 10.1186/s12911-022-01881-y
|View full text |Cite
|
Sign up to set email alerts
|

Health workers' use of routine health information and related factors at public health institutions in Illubabor Zone, Western Ethiopia

Abstract: Background Proper utilization of health data has paramount importance for health service management. However, it is less practiced in developing countries, including Ethiopia. Therefore, this study aimed to assess routine health information utilization and identify factors associated with it among health workers in the Illubabor zone, Western Ethiopia. Methods A facility based cross-sectional study was conducted from March to June 2021 with a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Organizational determinants address factors like resources, information culture, and management support. Technical determinants involve aspects such as data collection tools, processes, and systems availability [17][18][19][20][21][22][23] . The framework comprises four tools designed to assess or evaluate RHIS.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Organizational determinants address factors like resources, information culture, and management support. Technical determinants involve aspects such as data collection tools, processes, and systems availability [17][18][19][20][21][22][23] . The framework comprises four tools designed to assess or evaluate RHIS.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…In some African countries other than Ethiopia, it runs from 38% in Côte d'Ivoire to 69.6% in Kenya (10)(11)(12)(13)(14). The result of a systematic review in Ethiopia revealed that the overall utilization of data among care providers was 57.42% (15), which ranges from 45.8% in the East Gojjam Zone to 78.5% in North Gondar (16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that if locally available data are not well utilized, decisions to improve the performance of major health services may be distorted, contributing significantly to their low achievement ( 7 , 17 , 21 ). According to global SDGs ( 4 ) and the strategic plan of the Ethiopian health sector ( 22 ), maternal health services are identified as a prioritized area.…”
Section: Introductionmentioning
confidence: 99%